Comparative study of the Ar and He atmospheric pressure plasmas on E-cadherin protein regulation for plasma-mediated transdermal drug delivery. (30th April 2018) - Lee, Hyun Young; Choi, Jeong Hae; Hong, Jin Woo; Kim, Gyoo Cheon; Lee, Hae June
Abstract: The effects of argon plasma (ArP) and helium plasma (HeP) jets on E-cadherin protein function have been tested in order to choose the working gas for a better plasma-mediated transdermal drug delivery. The plasma-mediated changes of the E-cadherin function and the skin penetration efficacies of epidermal growth factor (EGF) were monitored in vitro using HaCaT human keratinocytes and in vivo using hairless mice. The ArP showed higher efficacy for E-cadherin regulation and EGF absorption than HeP under the same applied voltage and the same gas flow rate. The ArP generates higher volume power density, higher discharge current peak, and more reactive species than HeP, especially for OH with the same operating parameters. Moreover, the effect of ArP on E-cadherin function was blocked by the use of a grounded metal mesh. Taken together, this study presents the possibility that the synergetic effect of negative charges with radicals plays an important role in plasma-mediated E-cadherin regulation, which leads to enhanced transdermal drug delivery.